Implementasi Hukum Adat Sebagai Penanganan Restorative Justice Dalam Membangun Sistem Alternative Penyelesaian Hukum Pidana di Indonesia - Ternando, Albi; Alfarisi, M.s; Rahman, Rahman (Universitas Batanghari Jambi, 2023)
In the implementation of the resolution of criminal law violations in customary courts, it is felt to be very effective in dealing with many criminal cases through a restorative justice approach which theoretically relies on values that are characterized by Indonesian harmony, balance and conduciveness to ensuring shared life in society. Therefore, all forms of recognition of customary law must be carried out through acceptance and granting legal status related to the existence of its implementation in areas where the application of customary law is very strong. This research is a qualitative type of research with a normative conceptual and juridical approach. The data source was obtained by examining positive legal norms in the form of applicable laws and customary law norms. The conclusions that can be drawn from this research are: In customary justice it is not considered as non-formal justice outside of the judiciary under the State judiciary institution. The Supreme Court is on par with other customary justice bodies. Customary justice is something that actually occurs in the midst of society, therefore the basis contains the principles of restorative justice which focuses on resolving criminal cases outside of court so that the value of justice can be accepted by each group and individual in the customary law that occurs in Indonesian society.